Socialization of Women's Empowerment Through Creative Economy In The Crafts Sector - Ritonga, Zuriani; Zuhra, Fatimah; Maulana, Rizkha; Mulyadi, Mulyadi; Karimin, Karimin; Zhalikha, Zhalikha; Murniyanti, Sri (International Journal Of Community Service, 2025)
Socialization of Women's Empowerment Through Creative Economy in the Craft Sector" aims to increase women's awareness and skills in developing the creative economy in the craft sector. This activity is carried out through training and mentoring to improve women's abilities in designing, producing, and marketing craft products. The expected results are increased income and welfare of women, as well as the development of the creative economy in the community. Thus, this activity can contribute to women's empowerment and local economic development.